FAKTOR-FAKTOR GANGGUAN PADA KAWASAN SUAKA MARGASATWA KERUMUTAN DAN ALTERNATIF PENYELESAIAN BERDASARKAN PERSEPSI MASYARAKAT - Hamka Sari Budiman; Defri Yoza; M. Mardhiansyah M. Mardhiansyah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
Wildlife Reserve is a forest sanctuary to live wildlife which has a typical value and benefit to science and culture as well as a wealth and national pride. The condition of Kerumutan wildlife reserve region have been damaged, as it was need research on disturbances in the area ofwildlife reserve and approach to society to determine public perceptions in the completion of disruption that occurred in the area. Kerumutan Wildlife Reserve (WR) designated as protected areas by decree of the Minister of Agriculture No. 350/Kpts/II/6/1979.When designated size of the area is 120.000 ha. Once delineated, size of the area is 92.000 ha area with an additional 93.222 ha of land. Disruption that occurred last five years over is the disruption of illegal logging. Disturbance such wildlife hunting is no longer exist because it has maximal treatment used such arrest of the perpetrators and the container of fauna and alsothere was a difficulty of marketing on fauna. The disturbance of forest fires and land from the information obtained by the people and related offices occurred in the border area of  Kerumutan wildlife reserve. Forest and land fires are not happen within the region Kerumutan Wildlife reserve. As an alternative solution based on the perception of of society is the approach of the government to society, education or socialization of management policies and the society participated in the surveillance area, maximizing existing regulatory and human resources development.Keywords: Wildlife Reserve, Illegal logging, Society